A novel nutritional inflammation index for predicting mortality in acute ischemic stroke patients: insights into advanced lung cancer inflammation index from the Medical Information Mart for Intensive Care-IV database - Huang, Yongwei; Wang, Xiaoyi; Li, Zongping; Yin, Xiaoshuang (Frontiers in Nutrition, 2024)
Objective: This investigation aimed to delineate the association between the ALI and all-cause mortality in individuals experiencing acute ischemic stroke.Methods: Drawing on information from the MIMIC-IV database, covering the years 2012 to 2019, this research assessed the ALI by factoring in BMI, serum albumin levels, and the neutrophil-to-lymphocyte ratio. Patients with AIS were identified using codes from the ICD. To address potential confounding factors, a 1:1 PSM method was utilized. The investigation identified the pivotal ALI level impacting patient survival using maximally selected rank statistics. It then examined the effects on short-and long-term ACM through multivariate Cox proportional hazards regression models and Kaplan-Meier (K-M) survival analysis. Additionally, RCS methods were applied to delve into the linear or nonlinear nature of the relationship between ALI and ACM, with further insights gained from interaction and subgroup analyses.The cohort comprised 838 AIS patients. Post-PSM, analysis involved 199 matched patient pairs. Adjusted Cox proportional hazard models indicated a significant association of low ALI (< 10.38) with increased in-hospital ACM, both before (HR: 1.98; 95% CI: 1.36-2.88; P < 0.001) and after PSM (HR: 2.16; 95% CI: 1.32-3.52; P = 0.002).Associations of low ALI with elevated risk were consistent across ICU, 30 days, 90 days, and 1 year ACM pre-and post-PSM. Subsequent RCS analysis post-PSM underscored a negative nonlinear relationship between ALI and ACM over both short and long terms, without significant interaction effects across different subgroups for ACM.In this retrospective cohort study, by utilizing a nationally representative sample of United States patients with AIS, our analysis elucidates a negative correlation between the ALI and ACM in individuals with AIS, underscoring the utility of ALI as a novel, efficacious, and accessible inflammatory biomarker for prognosticating ACM. These results carry profound implications for public health policy and practice. A deeper comprehension of these associations can empower public health practitioners and researchers to devise more targeted interventions and policies, aimed specifically at catering to the distinct needs of the AIS patient population, thereby enhancing their health outcomes. The further research in other races/ethnicity is urgent, particularly before applying these findings in clinical practice.